An efficient template-independent polymerase chain displacement reaction for the detection of Salmonella typhimurium. Issue 35 (24th August 2018) - Wang, Jing; Li, Haigang; Li, Tingting; Zhang, Ji; Ling, Liansheng
Abstract : A template-independent and tailed tandem repeat-based polymerase chain displacement reaction (TTR-PCDR) was developed for the efficient detection of Salmonella typhimurium . Abstract : Here, we incorporated the tailed tandem repeat gene-specific primer technique into PCDR (TTR-PCDR), developing a template-independent PCDR which allows a rapid, one-tube reaction. Moreover, this TTR-PCDR was applied to the efficient detection of Salmonella typhimurium .